Intussusception due to cecal pericytoma hemangiography - Xavier, Artigas; Lizaso, Isabel; Klempert, Haydée; Altieri, Carlos (Cirugía del Uruguay, 1978)
A 13 -year- old child had to be treated for intestinal invagination caused by a hemangiopericytoma which is a rare tumor. After clinicar considerations and a review of the pathological anatomy of this tumor, the authors conelude that invaginations in older children and adults are generally symptomatic and always require surgical treatment. If the cause is a tumor, the latter is generally malignant and consequently the criteria applied should be oncological.